The Influence of the Integrated Education Program on the Psycho-Physical Readiness of Children for School Education - Nataliia Panhelova; Mariia Panhelova; Andriy Pyvovar; Vladislav Ruban; Tetiana Kravchenko; Nataliia Chuprun (Jan Długosz University in Częstochowa, 2023)
Modernization of preschool physical education is the subject of research by many scientists. The development and introduction of innovative recreation and health technologies into the practice of physical education in preschool education institutions is necessary in connection with the intensification of the educational load in the process of systematic preschool education, which increases the static component and negatively affects the physical condition of children and their readiness to school education. The implementation of existing physical culture and health technologies into the practice of physical education is slow. The purpose of the study is to implement and determine the impact of the comprehensive personality development program on the level of development of physical, cognitive abilities and speech of older preschoolers. Theoretical analysis and generalization of scientific and methodical literature, pedagogical, medical and biological methods, psychodiagnostic methods, methods of mathematical statistics were used in the study. Improvement of the content of physical culture and health work with older preschoolers in establishments of preschool education took place by introducing: innovative technologies of physical education, methods of psycho-prophylactic work, elements of tourist and local history activities, elements of sports-oriented physical education. These approaches were implemented through four blocks of physical exercise classes: physical education classes, physical culture andhealth activities during the day, active recreation, tourist and local history activities. Based on the determination of the means of combined development of motor and mental qualities, program material for the complex development of physical and cognitive abilities of older preschoolers in the process of physical education was developed.